2021
DOI: 10.1073/pnas.2018181118
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput functional variant screens via in vivo production of single-stranded DNA

Abstract: Creating and characterizing individual genetic variants remains limited in scale, compared to the tremendous variation both existing in nature and envisioned by genome engineers. Here we introduce retron library recombineering (RLR), a methodology for high-throughput functional screens that surpasses the scale and specificity of CRISPR-Cas methods. We use the targeted reverse-transcription activity of retrons to produce single-stranded DNA (ssDNA) in vivo, incorporating edits at >90% efficiency and enabling… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 69 publications
1
61
0
Order By: Relevance
“…Recently, several studies have shown that retrons coupled with CRISPR-Cas9 could enhance precise genome editing via HDR in bacterium and yeast through fusing guide RNA (gRNA) to the 3′ end of retron ncRNA, producing multicopy single-stranded DNA (msDNA) covalently tethered to gRNA (Sharon et al, 2018 ; Lim et al, 2020 ; Schubert et al, 2021 ). In this study, we further engineered retrons by fusing Cas9 with E. coli RT from different clades and joining gRNA at the 5′ end of retron ncRNA, and found that retron editing can achieve precise genome editing efficiently in human cells.…”
mentioning
confidence: 99%
“…Recently, several studies have shown that retrons coupled with CRISPR-Cas9 could enhance precise genome editing via HDR in bacterium and yeast through fusing guide RNA (gRNA) to the 3′ end of retron ncRNA, producing multicopy single-stranded DNA (msDNA) covalently tethered to gRNA (Sharon et al, 2018 ; Lim et al, 2020 ; Schubert et al, 2021 ). In this study, we further engineered retrons by fusing Cas9 with E. coli RT from different clades and joining gRNA at the 5′ end of retron ncRNA, and found that retron editing can achieve precise genome editing efficiently in human cells.…”
mentioning
confidence: 99%
“…By altering a part of msd-msr sequence, single-stranded DNA (ssDNA) containing desired mutations flanked by homology to a targeted genomic region could be produced in vivo . Retron-derived ssDNA has been demonstrated to facilitate template-mediated genome editing in yeast ( Sharon et al, 2018 ; Gallagher et al, 2020 ), mammalian cells ( Kong et al, 2021 ; Zhao et al, 2021 ), and bacteria ( Schubert et al, 2021 ). We fused the retron seq (msd-msr altered with donor sequence of interest) at the 5′ end of the gRNA to generate a chimeric transcript.…”
Section: Resultsmentioning
confidence: 99%
“…As technology advances at a breakneck pace, there are more unresolved issues and challenges surrounding gene therapy and the clinical products accessible today. Only a year after Jennifer Doudna and Emmanuelle Charpentier, the two pioneers of the revolutionary CRISPR tool, were awarded the 2020 Nobel Prize in Chemistry [ 208 ], a newer, superior alternative editing technology, Retron Library Recombineering (RLR), was introduced [ 209 ]. RLR, which can generate millions of mutations simultaneously, is regarded as a simpler, more flexible gene-editing tool that eliminates the toxicity frequently associated with CRISPR and improves researchers’ ability to investigate mutations at the genome level [ 209 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Only a year after Jennifer Doudna and Emmanuelle Charpentier, the two pioneers of the revolutionary CRISPR tool, were awarded the 2020 Nobel Prize in Chemistry [ 208 ], a newer, superior alternative editing technology, Retron Library Recombineering (RLR), was introduced [ 209 ]. RLR, which can generate millions of mutations simultaneously, is regarded as a simpler, more flexible gene-editing tool that eliminates the toxicity frequently associated with CRISPR and improves researchers’ ability to investigate mutations at the genome level [ 209 ]. Nevertheless, it is worth noting that before gene-editing tools such as CRISPR and RLR, other developed genetic technologies (such as in vitro fertilization, embryo cryopreservation, and preimplantation genetic diagnosis) have undergone similar criticisms, before being publicly approved and implemented on a large scale.…”
Section: Future Perspectivesmentioning
confidence: 99%